Diversity, biomass, and carbon stock of understorey plants in the rubber agroforestry and rubber monoculture systems in Central Tapanuli District, North Sumatra, Indonesia - Muhdi Muhdi; DIANA SOFIA HANAFIAH; RITA DESPRIANA BUTAR-BUTAR (Society for Indonesian Biodiversity, 2020)
Abstract. Muhdi, Hanafiah DS, Butar-Butar RD. 2020. Diversity, biomass, and carbon stock of understorey plants in the rubber agroforestry and rubber monoculture systems in Central Tapanuli District, North Sumatra, Indonesia. Biodiversitas 21: 3508-3518. Understorey vegetation plays an important role in carbon stock in forest. The objectives of the research were to identify the species of understorey, to find out the amount of carbon stored in the understorey, and to compare the understorey carbon stocks in rubber agroforestry and rubber monoculture. The research was done in Sijungkang Village, Andam Dewi Sub-district, District of Central Tapanuli and Forest Products Chemistry Laboratory, Faculty of Forestry, IPB University on August-October 2016. The method used was the plant vegetation analysis of a stand and understorey. Destructive sampling method was used to harvest of understorey plant in 1 m × 1 m sample plot. The carbon of understorey was analyzed by independent sample t-test. The results showed that there were 23 species in rubber agroforestry and 15 species in rubber monoculture. The understorey species dominant of rubber agroforestry was Stachytarpheta jamaicensis and rubber monoculture was Asystasia gangetica with important value index 30.64% and 33.01%, respectively. The average understorey plant biomass in rubber monoculture was 0.94 tons/ha and in rubber agroforestry were 0.84 tons/ha, respectively. The carbon stocks of understorey in rubber agroforestry were 0.21 tons/ha and in rubber monoculture were 0.25 tons/ha, respectively. The result of t-test showed that there is not significant difference between carbon stock of understorey in rubber agroforestry and rubber monoculture.